Effect of no-tillage on soil bacterial and fungal community diversity: A meta-analysis - Li, Yüze; Song, Duanpu; Liang, Shihan; Dang, Pengfei; Qin, Xiaoliang; Liao, Yuncheng; Siddique, Kadambot H.M. (Soil & tillage research, 2020)
[Display omitted] •No-tillage increases soil bacterial diversity and had no significant effect on fungal diversity.•Effect of no-tillage on microbial diversity is affected by soil type and stubble retention.•Nitrogen application (100–200 kg ha–1) increased soil microbial diversity under no-tillage.•Retaining stubble under no-tillage had better effect on soil microbial diversity. No-tillage farming is widespread globally; however, the impact of no-tillage on soil microbial diversity is debatable. The existing research literature needs to be synthesized and a comprehensive and unified standard analysis conducted to examine the effects of no-tillage on soil microbial diversity. To this end, we conducted a meta-analysis based on 43 peer-reviewed articles from around the world, with 141 observations on microbial community changes under no-tillage. No-tillage had different effects on bacterial and fungal community diversity—increasing soil bacterial diversity, with no significant change to fungal diversity—and soil type and stubble had a significant impact on soil bacterial diversity. Neither low (0–100 kg ha–1) nor high (> 200 kg ha–1) nitrogen applications could simultaneously promote soil organic carbon and total nitrogen under no-tillage, but a medium (100–200 kg ha–1) nitrogen application level accomplished this goal. A medium nitrogen application level significantly changed soil microbial diversity under no-tillage, while excessively high or low nitrogen application levels had no significant effect. No-tillage significantly increased the relative abundance of Acidobacteria, decreased Actinobacteria, and had little effect on Proteobacteria, Chloroflex, Firmicute, and Bacteroides. A structural equation model showed that retaining stubble under no-tillage had the most significant effect on soil microbial diversity by changing soil organic carbon and total nitrogen contents. Field management with long-term no-tillage, stubble, and medium nitrogen application can improve soil bacterial diversity.